Usability Analysis using User Experience Questionnare (UEQ) and Concurrent Think Aloud (CTA) on Fintech Bibit Application (Case Study on Bibit Application Users in Denpasar) - AA Istri Ita Paramitha (STMIK Pringsewu, 2023)
This study aims to measure and determine the effectiveness, efficiency and user satisfaction of the Bibit fintech application. The results of measurements carried out using Concurrent Think Aloud show that the effectiveness measurement obtains an average result of 90% and the efficiency measurement obtains an average result of 91%. The results of measuring user satisfaction can be obtained from the results of the User Experience Questionnaire aspects of efficiency (1.68) aspects of attractiveness (1.39), perspicuity (1.40), stimulation (1.21) dependability (1.00) and novelty (0.48) . This research shows that the Fintech Seeds application has been effective and efficient in its use, and on user satisfaction it has a positive impression, only that the novelty aspect has neutral results, thus innovation and creativity in development must increase in the future.